The Sinking Heart: A case of left anterior descending artery intervention complicated by perforation and cardiac tamponade - Grigorov, Mladen (Glob Cardiol Sci Pract, 2020)
Coronary interventions are one of the most commonly performed procedures in interventional medicine. They have provided a life-prolonging and -saving solution, but are not without their own complications. These, although rare, do occur and are important to recognize in order to promptly and efficiently provide a solution to prevent catastrophic consequences to the patient. We present a 70-year-old male with a past medical history significant for hypertension, hyperlipidemia, and myasthenia gravis; who presented to the hospital with substernal, pressure-like chest pain with associated nausea and diaphoresis. He was found to have ST segment elevations in anterolateral leads, prompting catherization lab activation revealing left anterior descending (LAD) artery stenosis. Percutaneous intervention via balloon dilation and stent placement was performed with periprocedural mid-intervention hemodynamic collapse occurring. Subsequent left ventricular (LV) angiography was performed revealing preserved LV function without perforation - however a rim of contrast was noted surrounding the LV. Thus, hemodynamic collapse was recognized as result of cardiac tamponade with pericardial drain emergently inserted resulting in hemodynamic recovery. Our case aims to present a case of vascular perforation with the uniqueness in our diagnostic approach via fluoroscopic imaging.